The effect of revenue diversification on bank profitability and stability during the COVID-19 Pandemic: Evidence from Kenya - Rogers Ochenge (Kenya Bankers Association (KBA), 2022)
This paper uses annual data from Kenyan banks over the 2010-2020 period to empirically analyze the link between diversification (non-interest income) and bank performance. Using dynamic panel regressions, the study finds that banks which diversify (functionally) their sources of revenues tend to be more profitable and financially stable. Importantly, the study finds that reliance on non-interest revenue sources acts as an economically important shock absorber in times of declining profits such as witnessed in the ongoing COVID-19 pandemic. From a policy perspective, these results encourage banks to leverage on new technologies to create non-traditional products whose operating marginal costs are small. This also calls for regulators to remain open to such innovations.
Keywords: 330